Isolation, Characterization, and Optimization of Culture Medium for Local Straw-Degrading Bacteria from Northeastern Black Soils of China - Lei Zhang; Tianyu Liu; Chengzhao Yan; Jinpeng Zhang; Rui Yu; Nana Luo; Yong Yu (Agronomy)
In order to solve the problem of low and poor straw degradation in typical black soil areas of Northeast China, the present study was carried out to screen the potential of in situ strains with cellulose degradation ability from black soils of Northeast China to play a role in the resourceful utilization of straw and the development of sustainable agriculture. The straw degradation potential of the strains was evaluated by combining sodium carboxymethyl cellulose plate screening and cellulase viability assay; the species identification of the strains was carried out by morphology, physiology, biochemistry, and molecular biology; and the basic medium formulation of the strains was optimized by Box–Behnken response surface methodology. Ten cellulose-degrading strains were identified: ZL-5, ZL-69, ZL-88, ZL-95, ZL-111, ZL-137, ZL-139, ZL-140, ZL-187, and ZL-216, of which ZL-139 had the highest cellulase production capacity, with a cellulase secretion of 7.8781 U/mL in the enzyme-producing medium. ZL-139 was identified as Bacillus cereus; the optimized best formulation was glucose—4.284 g/L, yeast extract—1.454 g/L, MgSO4—0.417 g/L, KH2PO4—0.5 g/L, KH2PO4—0.5 g/L, K2HPO4—1.5 g/L, and NaCl—1.0 g/L. In conclusion, strain ZL-139 has good potential for crop straw degradation and can be a candidate strain for a straw-rotting agent in northeast China, with promising prospects for development and utilization.